Les différentes versions de la « découverte » du clitoris par Helen O’Connell (1998-2005) - Alessandra Cencin (Genre, Sexualité et Société)
Between 1998 and 2005, Australian urologist Helen E. O’Connell published a series of scientific articles about her research on the anatomy of the clitoris. In a singular way, she presented her results in a critical narrative denouncing a production of anatomical knowledge biased in terms of gender. After presenting the issues of this research, such as the visual representation of the clitoris, this article looks at the media popularization, which qualified these results as a “discovery.” Finally, this article also questions this reception and the question of the multiple historical claims to the discovery of the female organ. The analysis of narratives circulating in different contexts of knowledge production illuminates a (re-) signification of the clitoris, and by extension of female sexuality, at the turn of the twenty-first century.